Biological control of the invasive wasp Vespula germanica in Australia: Assessing socio-economic feasibility - Susan M. Hester; Peter Tait; Raelene Kwong; Greg Lefoe; Darren Kriticos; Oscar J. Cacho (Ecological Economics, 2024)

Mycena species can be opportunist‐generalist plant root invaders - Christoffer Bugge Harder; Emily Hesling; Synnøve S. Botnen; Kelsey E. Lorberau; Bálint Dima; Tea von Bonsdorff‐Salminen; Tuula Niskanen; Susan G. Jarvis; Andrew Ouimette; Alison Hester; Erik A. Hobbie; Andy F. S. Taylor; et al. (Environmental Microbiology, 2023)
Traditional strict separation of fungi into ecological niches as mutualist, parasite or saprotroph is increasingly called into question. Sequences of assumed saprotrophs have been amplified from plant root interiors, and several saprotrophic genera can invade and interact with host plants in laboratory growth experiments. However, it is uncertain if root invasion by saprotrophic fungi is a widespread phenomenon and if laboratory interactions mirror field conditions. Here, we focused on the widespread and speciose saprotrophic genus Mycena and performed (1) a systematic survey of their occurrences (in ITS1/ITS2 datasets) in mycorrhizal roots of 10 plant species, and (2) an analysis of natural abundances of 13 C/ 15 N stable isotope signatures of Mycena basidiocarps from five field locations to examine their trophic status. We found that Mycena was the only saprotrophic genus consistently found in 9 out of 10 plant host roots, with no indication that the host roots were senescent or otherwise vulnerable. Furthermore, Mycena basidiocarps displayed isotopic signatures consistent with published 13 C/ 15 N profiles of both saprotrophic and mutualistic lifestyles, supporting earlier laboratory‐based studies. We argue that Mycena are widespread latent invaders of healthy plant roots and that Mycena species may form a spectrum of interactions besides saprotrophy also in the field.

The contribution of passive surveillance to invasive species management - Susan M. Hester; Oscar J. Cacho (Biological Invasions, 2017)

Evaluating the Feasibility of Eradicating an Invasion - J. Oscar Cacho; Daniel Spring; Paul Pheloung; Susan Hester (Biological Invasions, 2006)